Obtenção de limitantes superiores para o problema de dimensionamento de lotes em máquinas paralelas - Apolinário, Leonardo Andrade (2020)
When dealing with production planning, lot-sizing problems are considered as very important to the literature. This work considers the Multi Item Capacitated Lot-sizing Problem with Unrelated Parallel Machines. This problem consists of determining an optimal production plan such that the demands are satisfied, the machine capacities are not exceeded and the total cost is minimized. The objective is to obtain good feasible solutions by proposing two approaches combining the relax-and-fix and fix-and-optimize heuristics. Both approaches are compared to other approaches available in the literature. The results show that the obtained solutions are in average better than those found in the literature in terms of optimality gaps